PUBLIC INFORMATION CAMPAIGN MANAGEMENT BY BAZNAS PROVINSI SUMATERA BARAT - Qatrinnada Anistina Elsafrediniya (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
In carrying out the task of managing zakat, BAZNAS Provinsi Sumatera Barat conducts Public Information Campaign activities in this research in the form of socialization. However, after the socialization activities were carried out the response from the target did not match what was expected. Response that is not in line with expectations can indicate that there is a problem in the activity process. This study aims to explain the management of the Public Information Campaign by using the theory of Planning and Managing Public Relations Campaign by Anne Gregory that apply in BAZNAS Provinsi Sumatera Barat. This research was conducted using a qualitative method. The results of the study indicate that the management activities of the Public Information Campaign by BAZNAS of West Sumatra Province have been running quite well. The form of the campaign carried out is still face to face and has not utilized mass media or new technology.